Comparison of Online Gambling Legal Regulations Between Indonesia and The United States - Darmawan, Nino Gilang; Tumanggor, MS; Hakim, Lukman (Siber International Journal of Advanced Law (SIJAL), 2026)
Gambling in Indonesia has historically been a social ill strictly prohibited by various regulations, such as Article 303 of the Criminal Code, Law No. 7 of 1974, and the Electronic Information and Transactions (ITE) Law. However, a legal dualism currently exists , where gambling is prohibited for moral and religious reasons, while a legal loophole exists through the terms "without permission" and "without rights" in the law. This loophole manifests itself in the legality of business permits for gambling and betting activities (such as casinos, slot machines, and online games ) under KBLI codes 9200 and 92000 through the business licensing system . The regulation of online gambling in Indonesia demonstrates inconsistencies compared to the United States, which strictly enforces regional (state)-based regulations. In Indonesia, there is a contradiction between the spirit of eradicating gambling and the emergence of legal business permits within the standard business classification. Therefore, a special review and regulatory improvement are needed by the government and legislative bodies to close this legal loophole and prevent misuse by irresponsible parties